2022
DOI: 10.1111/cob.12531
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating disorder and eating self‐efficacy in adults seeking bariatric surgery

Abstract: This study assessed the relationships between binge eating disorder (BED) and eating self-efficacy in a sample of patients prior to bariatric surgery. The study also examined the extent that BED status accounted for variance in self-efficacy after controlling for demographic factors (age, sex and race), physical variables (comorbidities and body mass index [BMI]) and depressive symptoms. This was a cross-sectional study of pre-surgical data from patients seeking bariatric surgery at a university-based healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…(2022) [33]found that among patients seeking bariatric surgery, those diagnosed with Binge Eating Disorder (BED) had signi cantly lower scores on the eating self-e cacy subscales, including control over negative emotions and social pressure, compared to those without BED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) [33]found that among patients seeking bariatric surgery, those diagnosed with Binge Eating Disorder (BED) had signi cantly lower scores on the eating self-e cacy subscales, including control over negative emotions and social pressure, compared to those without BED.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies reported reduced eating self-e cacy in individuals with Binge Eating Disorder (BED) when facing situations characterized by negative emotions or physical discomfort, as compared to people without this diagnosis [e.g. [12][13][14].…”
Section: Introductionmentioning
confidence: 99%